Speech-language pathologist’s knowledge about hearing aid performance measurements: a survey - Ubaidillah, Engku Salma Engku (Universiti Sains Malaysia, 2012)
Hearing impairment can lead to serious consequences in one life especially to those prelingual hearing losses. Based on current technologies, those hearing impaired can be fitted with hearing aids and sent to Speech-Language Pathologist for aural rehab. The hearing aid fitted to them need to be verified whether the HA is giving enough gain or is working properly. There are 3 main ways to access the performance of the HA, that is by using 2cc coupler measurement, functional gain, and real-ear measurements (REM). SLPs need to have the knowledge and skills to address the complex interplay of the areas of listening, speaking, signing, reading, writing, and thinking. Furthermore, they should understand how skill expansion in one of these components enhances performance in another area ultimately contributing to the overall development of literacy and learning. The objective of this survey is to determine an overall view about SLP’s knowledge regarding hearing aids performance measurements. A questionnaire was developed to achieve the objective. This questionnaire had been validated using Cronbach’s alpha (a=0.920 for Part B and a=0.945 for Part C). 102 questionnaires were sent to the SLPs however only 38 of them replied back. From 53% of the SLPs that seeing hearing impaired patients on daily basis, 49% of them said that HA performance measurement is to check whether HA is giving enough gain. 38% of them know types of HA performance measurement but 72% of them are unsure of how many types of test are there to measure HA performance. From the study we can conclude that most of the SLPs preferred aided response compared to REM. It is the utmost test that they are familiar and are most understandable compared to other test available. We can also conclude that they have little knowledge about REM compared to aided response.